Generalized Halpern-type forward–backward splitting methods for convex minimization problems with application to image restoration problems. (2nd August 2020) - Kitkuan, Duangkamon; Kumam, Poom; Martínez-Moreno, Juan
ABSTRACT: In this work, our interest is to investigate the monotone inclusion problem in the framework of real Hilbert spaces. For solving the inclusion problem, we propose a composite iteration for approximating a zero of sum of two operators. We prove its strong convergence under some mild conditions. Finally, we provide a number of applications to convex minimization and image restoration problems including numerical experiments to support our main theorem.